Hyperuricemia and hypertension - Rapicka, Dorota; Fabian-Danielewska, Anna (Journal of Education, Health and Sport, 2019)
Hiperuricemia is associated mostly with gout and urolithiasis. However, it is now known that it affects a number of other health problems. It plays an important role in the development of hypertension, metabolic syndrome and other cardiovascular diseases. In addition, the relationship between hyperuricemia and obesity, hyperlipidemia, stroke and vascular dementia, renal disease, obstructive sleep apnea and insulin resistance has been proven. Increased serum uric acid is a risk factor for cardiovascular disease and contributes to increased mortality in patients with ischemic heart disease. The preferred drugs for the treatment of hypertension with increased uric acid concentration are calcium channel blockers (urinary properties) and losartan. From diuretics aldosterone antagonists are prefered. Other blockers of the angiotensin receptor should be avoided because they reduce the excretion of uric acid by the kidneys. B-blockers, thiazide and loop diuretics, ACE inhibitors are also inadvisable.